2022
DOI: 10.1590/1981-7746-ojs616
|View full text |Cite
|
Sign up to set email alerts
|

Barreiras de acesso à Atenção Primária à Saúde em municípios rurais remotos do Oeste do Pará

Abstract: Resumo Analisa-se neste artigo o acesso à Atenção Primária à Saúde em municípios rurais remotos do Oeste do Pará, discutindo barreiras e desafios ante as especificidades dos territórios amazônicos. Tratou-se de estudo qualitativo em cinco municípios com lógicas espaciais distintas, assentadas em rios ou estradas. Realizaram-se 58 entrevistas com gestores, profissionais da saúde e usuários, além de visitas a unidades básicas de saúde, em 2019. A matriz de análise contemplou: acessibilidade geográfica, acessibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 20 publications
(13 reference statements)
0
1
0
6
Order By: Relevance
“…Our results demonstrate that workers in both primary healthcare and surveillance face considerable obstacles that extend through patient flow, professional conduct, work structure, material availability, provision of training on leptospirosis, and lack of protocols. The disease's lack of visibility results in workers and the population's unawareness of prevention methods, contamination, and diagnosis 23,24 . The study revealed insufficient knowledge about leptospirosis and prevention and control measures in primary care, as acknowledged in participants' statements, particularly in the discourse of Community Health Agents (CHAs).…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that workers in both primary healthcare and surveillance face considerable obstacles that extend through patient flow, professional conduct, work structure, material availability, provision of training on leptospirosis, and lack of protocols. The disease's lack of visibility results in workers and the population's unawareness of prevention methods, contamination, and diagnosis 23,24 . The study revealed insufficient knowledge about leptospirosis and prevention and control measures in primary care, as acknowledged in participants' statements, particularly in the discourse of Community Health Agents (CHAs).…”
Section: Discussionmentioning
confidence: 99%
“…Acima de tudo, as barreiras geográficas não devem ser obstáculos ao acesso de políticas públicas e à garantia do direito ao acesso à saúde no Sistema Único de Saúde (Garnello et al, 2018). Dessa forma, o reconhecimento das especificidades geográficas deve nortear o planejamento e a formulação de estratégias inovadoras que busquem superar os desafios geográficos (Lima et al, 2022).…”
Section: Estadosunclassified
“…A Amazônia Legal corresponde à delimitação geográfica em que a Superintendência do Desenvolvimento da Amazônia (SUDAM) atua e esta, por sua vez, faz seu papel na sustentabilidade e integração da floresta nas economias nacionais e internacionais. Nessa área, habitam milhões de pessoas em circunstâncias sociais, políticas e econômicas adversas, as quais, não raro, são desprovidas de auxílio adequado dos profissionais da saúde, devido às especificidades geográficas e à carência de estratégias direcionadas para oferta e organização dos serviços 4 .…”
Section: Introductionunclassified